2005
DOI: 10.1007/s00125-005-1900-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes in brain glucose metabolism during hypoglycaemia accompany loss of hypoglycaemia awareness in men with type 1 diabetes mellitus. An [11C]-3-O-methyl-d-glucose PET study

Abstract: Differential changes in brain glucose metabolism during hypoglycaemia accompany loss of hypoglycaemia awareness in men with type 1 diabetes mellitus. An Abstract Aims/hypothesis: Hypoglycaemia unawareness in type 1 diabetes increases the risk of severe hypoglycaemia and impairs quality of life for people with diabetes. To explore the central mechanisms of hypoglycaemia awareness, we used [ 11 C]-3-O-methyl-D-glucose (CMG) positron emission tomography (PET) to measure changes in global and regional brain glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 56 publications
0
47
0
2
Order By: Relevance
“…Hypoglycemic syncope is reported as isolated experiences [7]. Metabolic syncope is comprising about 5% of all syncope.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoglycemic syncope is reported as isolated experiences [7]. Metabolic syncope is comprising about 5% of all syncope.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic syncope is comprising about 5% of all syncope. Hypoglycemic syncope is the most common metabolic syncope, with a reported incidence of 0.6% in diabetic patients and 4% in diabetic patients who take insulin [7]. Instead, the true incidence of hypoglycemic syncope is unknown due to the lack of established diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed a reduced activation in left temporal lobe white matter, splenium and body of the corpus callosum of controls as compared with patients. While the involvement of these white matter areas is potentially interesting, the significance of the difference between the groups disappeared in such regions when a large cluster equal to that of other investigators was used for analysis, 1,4,6,7,12 in contrast to what observed in the thalamus. This observation raises questions about the robustness of the findings in the white-matter regions.…”
Section: Discussionmentioning
confidence: 96%
“…14 Meanwhile, working simultaneously on a different NIHR programme grant, the research group attached to the King's College Hospital DAFNE centre had continued to investigate the pathophysiology of impaired hypoglycaemia awareness and problematic hypoglycaemia resistant to intervention. Bingham et al 117 and Dunn et al…”
Section: Introductionmentioning
confidence: 99%